2017
DOI: 10.1002/cncr.31184
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in children with acute lymphoblastic leukemia

Abstract: BMD Z-scores decreased during therapy, especially in patients who had clinical, pharmacokinetic, and genetic risk factors. Early recognition of BMD changes and strategies to optimize bone health are essential. Cancer 2018;124:1025-35. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 43 publications
3
19
0
2
Order By: Relevance
“…Low BMD in pediatric cancer survivors has been reported previously, but the majority have been reported in ALL cases . Inaba et al reported reduced BMD Z ‐scores in patients with ALL during therapy and only partly recovered after 2 years off therapy. Although the BMD Z ‐scores were enhanced after completing treatment, they remained lower than those at diagnosis .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Low BMD in pediatric cancer survivors has been reported previously, but the majority have been reported in ALL cases . Inaba et al reported reduced BMD Z ‐scores in patients with ALL during therapy and only partly recovered after 2 years off therapy. Although the BMD Z ‐scores were enhanced after completing treatment, they remained lower than those at diagnosis .…”
Section: Discussionmentioning
confidence: 92%
“…A specific diagnosis referring to metabolic bone disease in the preterm infant is osteopenia of prematurity, which is not based on BMD Z ‐score . One radiological study defined BMD Z ‐scores < −2 and between −1 and −2 as severe and mild osteopenia, respectively, while a recent St. Jude cohort regarding BMD in childhood ALL defined BMD Z ‐scores < −1.5 as low BMD . In our study, we gave denosumab therapy only for the patients who had persistently BMD Z ‐scores < −1.5 even after calcium and vitamin D supplementation.…”
Section: Discussionmentioning
confidence: 95%
“…Examination of Masson's Trichrome-stained sections of MTX-treated group showed thin discontinuous bony trabeculae which were formed mostly of unmineralized bone matrix with few areas of mineralized bone matrix. Previous findings were reported by [25] who confirmed that, children with ALL showed a significant decrease in the bone mineral density (BMD) after MTX-chemotherapy. [26] explained that MTX-induced osteoblastic damage caused diminished mineralizing surface, mineral apposition rate and bone formation rate.…”
Section: Discussionmentioning
confidence: 67%
“…По данным литературы, гемобластозы являются распространенным фактором риска развития вторичного остеопороза и низкоэнергетических переломов [5]. Остеопороз и остеопения, как осложнения терапии лимфопролиферативных заболеваний, чаще встречаются у больных ЛХ (до 88 % пациентов), чем у больных неходжкинскими лимфомами (67 %) и хроническим лимфоцитарным лейкозом (49 %) [7].…”
Section: Discussionunclassified